Field Level RNAi-Mediated Resistance to Cassava Brown Streak Disease across Multiple Cropping Cycles and Diverse East African Agro-Ecological Locations - Wagaba, Henry; Beyene, Getu; Aleu, Jude; Odipio, John; Okao-Okuja, Geoffrey; Chauhan, Raj Deepika; Munga, Theresia; Obiero, Hannington; Halsey, Mark E.; Ilyas, Muhammad; Raymond, Peter; Bua, Anton; et al. (Frontiers in Plant Science, 2017)
Cassava brown streak disease (CBSD) presents a serious threat to cassava production in East and Central Africa. Currently, no cultivars with high levels of resistance to CBSD are available to farmers. Transgenic RNAi technology was employed to combat CBSD by fusing coat protein (CP) sequences from Ugandan cassava brown streak virus (UCBSV) and Cassava brown streak virus (CBSV) to create an inverted repeat construct (p5001) driven by the constitutive Cassava vein mosaic virus promoter. Twenty-five plant lines of cultivar TME 204 expressing varying levels of small interfering RNAs (siRNAs) were established in confined field trials (CFTs) in Uganda and Kenya. Within an initial CFT at Namulonge, Uganda, non-transgenic TME 204 plants developed foliar and storage root CBSD incidences at 96-100% by 12 months after planting. In contrast, 16 of the 25 p5001 transgenic lines showed no foliar symptoms and had less than 8% of their storage roots symptomatic for CBSD. A direct positive correlation was seen between levels of resistance to CBSD and expression of transgenic CP-derived siRNAs. A subsequent CFT was established at Namulonge using stem cuttings from the initial trial. All transgenic lines established remained asymptomatic for CBSD, while 98% of the non-transgenic TME 204 stake-derived plants developed storage roots symptomatic for CBSD. Similarly, very high levels of resistance to CBSD were demonstrated by TME 204 p5001 RNAi lines grown within a CFT over a full cropping cycle at Mtwapa, coastal Kenya. Sequence analysis of CBSD causal viruses present at the trial sites showed that the transgenic lines were exposed to both CBSV and UCBSV, and that the sequenced isolates shared >90% CP identity with transgenic CP sequences expressed by the p5001 inverted repeat expression cassette. These results demonstrate very high levels of field resistance to CBSD conferred by the p5001 RNAi construct at diverse agro-ecological locations, and across the vegetative cropping cycle.